Do personal characteristics of finance ministers affect the development of public debt? - Marc-Daniel Moessinger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
Using a unique dataset of personal characteristics of national finance ministers in Europe (1980 - 2010), I show that especially a finance minister's experience affects the development of public debt. Both a finance minister's experience gained in office and his political experience have an impact: The change of the debt to GDP ratio is negative the more experience a finance minister has gained as a minister of finance or in former positions as a national cabinet member. While the former result suffers from potential endogeneity, several arguments support that the latter result can be interpreted in a causal way. In contrast, a finance minister's educational background or ideology have no significant impact on public debt changes.
urn:nbn:de:bsz:180-madoc-326209
Keywords: D78; H30; H62; 330; public finance; public debt; finance minister; personal characteristics